The Effect of Online Delivery of the MS-Get-a-Head-Start Programme on Physical Activity and Exercise Self-Efficacy in People with Multiple Sclerosis: A Feasibility Study and Pilot Randomised Controlled Trial - Davy, Gillian (Auckland University of Technology, 2026)
New Zealand has a higher-than-average global prevalence of multiple sclerosis. This prevalence has significantly risen in the last decade and is likely to continue to rise in line with global trends. Despite the well-documented benefits of regular physical activity for people with multiple sclerosis, levels of inactivity within this population remain high. This highlights the pressing need for accessible and tailored physical activity programmes specifically designed to support people with multiple sclerosis. Accurate information on physical activity is one of the highest unmet needs of people with multiple sclerosis. To improve accessibility there has been an increase in online delivery of exercise programmes, however, to date these all still require therapist interaction through the programme. The online MS Get a Head Start programme is one of the first fully automated exercise and education programmes for people with multiple sclerosis. It is a six-week programme incorporating interval-based exercise, education and behaviour change strategies aimed at enhancing the capacity and confidence of people with multiple sclerosis to engage in exercise and physical activity. A pilot study was completed measuring the feasibility and safety of the online MS Get a Head Start programme as well as the impact on self-reported physical activity levels and exercise self-efficacy. Thirty-five people with multiple sclerosis were randomised to the intervention or waitlist control group. The intervention group received two exercise and one education video weekly for six weeks, plus goal setting and self-reflection course work. Feasibility, self-reported physical activity, and exercise self-efficacy, were assessed at baseline, week seven, and week twelve. Feasibility outcomes indicated that recruitment to the study was highly successful, reflecting strong interest and demand for an online exercise programme among people with multiple sclerosis in New Zealand. The intervention was found to both useful and easy to use by the participants, and importantly, no adverse events attributable to the programme were observed, supporting its safety. However, the study had a substantial loss to follow-up within the intervention group. The pilot study was not powered to find significance. Physical activity levels remained consistent, although both groups demonstrated a decline in exercise self-efficacy across the study, contrary to the initial hypothesis that the programme would strengthen participants’ confidence in their ability to exercise. Taken together, these findings suggest that the online MS Get a Head Start programme is safe, acceptable, and feasible to deliver in an online automated format to reach more people living with multiple sclerosis across New Zealand. However, further refinement is required before progressing to a larger scale randomised controlled trial.